A COMPARATIVE STUDY OF PRE-COMPETITIVE ANXIETY LEVEL BETWEEN MALE AND FEMALE INTERCOLLEGIATE BASEBALL PLAYERS OF GOA - Mahadevan, Suman; Prajakta Halankar (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2021)
Competitive state anxiety that occurs prior to the competitive situation is referred to as Pre Competitive Anxiety. The purpose of this descriptive comparative study was to find out the Pre Competitive Anxiety level between male and female intercollegiate baseball players of Goa. For which 200 sample were selected. The sample for the study had been selected based upon non probability based purposive sampling technique out of which 100 male and 100 female intercollegiate baseball players who had participated in intercollegiate baseball tournament organised by goa university in the year 2019-20, the age of the player is 18-25 years, and the one who had 2 years playing experience in intercollegiate baseball tournament. The data was collected with the help of Sports Competitive Anxiety Test (SCAT) standardized by Martens (1977) in the form of paper pencil test. The test contains 10 items, 10 of which measures symptoms associated with anxiety of the players. In which the score is normalised on the 3-point scale (Rarely 1, Sometimes 2 and Often 3) wherein (0-17) being the low competitive anxiety and (24-40) being the high Competitive Anxiety. Further the data was analysed, the calculated mean value of comparing Pre Competitive Anxiety among male and female intercollegiate baseball players was 33.32 and 35.11. Further for analysing data independent sample T test was computed. The calculated t value is 2.994, the result shows the calculated t value has a significant difference at 0.05 level of significance (p= .003) hence this study can be concluded that there is a significant difference in Pre Competitive Anxiety of male and female intercollegiate baseball players of goa. The study conclude that men baseball players had less anxiety than that of women interuniversity baseball players of goa.